2015
DOI: 10.4236/ojpathology.2015.53011
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Activity of Olive Oil (Olea europaea) against High Fat Diet-Induced Nonalcoholic Fatty Liver Disease (NAFLD) in Mice

Abstract: Aim: The aim of the present study is to access the effect of olive oil supplementation against high fat diet induced fatty liver disease in mice. Methods: Mice were divided into five groups: Group I (normal diet), Group II (high fat diet), Group III (olive oil), Group IV and V (High Fat Diet along with olive oil). All mice were fed for 16 weeks with weight measurements every 2 weeks and then sacrificed. Biochemical analysis of blood samples was done and mice livers were histologically examined. Results: Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…Our results are also similar with Necib et al (2013) who reported significant (P<0.01) decreased in the serum ALT activities after treating the rats with olive oil 2 ml. The variable effects of olive oil supplementation on biochemical constituents of Teddy buck and other animals or bird might be due to variation in enzymatic differences in the digestive process Our results shown that serum triglyceride significantly decrease (P<0.05) as compared to untreated group which are in line with Wani et al (2015) who reported the consequence of olive oil in contradiction of high fat diet in mice. The significant (P<0.05) reduction in triglycerides level in olive oil groups linked to assembly treated with high fat diet.…”
Section: Table 1 Serum Biochemical Metabolites and Hormonal Profile supporting
confidence: 89%
“…Our results are also similar with Necib et al (2013) who reported significant (P<0.01) decreased in the serum ALT activities after treating the rats with olive oil 2 ml. The variable effects of olive oil supplementation on biochemical constituents of Teddy buck and other animals or bird might be due to variation in enzymatic differences in the digestive process Our results shown that serum triglyceride significantly decrease (P<0.05) as compared to untreated group which are in line with Wani et al (2015) who reported the consequence of olive oil in contradiction of high fat diet in mice. The significant (P<0.05) reduction in triglycerides level in olive oil groups linked to assembly treated with high fat diet.…”
Section: Table 1 Serum Biochemical Metabolites and Hormonal Profile supporting
confidence: 89%
“…In the present study, PO lowered serum TG levels without affecting serum TC levels. According to a previous report, OO has hypolipidemic activity [ 21 ]. In the present study, compared with HFD, HOO group showed reduced TG levels, however TC level was not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Our results using olive oil are comparable to previous studies using different animal models [ 40 43 ]. For example, Wani et al [ 42 ] induced hepatic steatosis in mice using a high fat diet (42 % of energy as fat; over 16 weeks). Administration of olive oil with the high fat diet decreased weight gain, serum triglycerides, normalized liver enzyme levels, and decreased hepatic steatosis.…”
Section: Discussionmentioning
confidence: 99%